(untitled) (Web of Teachers: Inderscience Research, 2024)
The differences between these cultures lead to certain difficulties in communication. These difficulties are due to differences in expectations and prejudices that are inherent in each person, and, naturally, differ in different cultures. The language reflects the usual patterns of thinking, models of perception of reality, the experience of cognition of the world accumulated in culture. Linguistic problems are often the first difficulties in communicating with representatives of other cultures.